EFFECT OF RELIABILITY AND VALIDITY TESTING IN GUIDANCE AND COUNSELING RESEARCH - Mauladi, Tiara Anggun; Ahman, Ahman; Morteza, Recita Widyan; Fahriza, Febi Dwi; Aripin, Samsul (OPTIMA: Journal Of Guidance and Counseling, 2025)
Reliability and validity testing are essential steps in guidance and counseling research to ensure the quality of research instruments. This study aims to analyze the effect of reliability and validity testing on the quality of research results in the field of guidance and counseling. The method used is a systematic literature review (SLR) by analyzing 10 articles published in the period 2020-2024. The results show that valid and reliable instruments contribute significantly to the accuracy, consistency, and relevance of research data. Validity ensures that the instrument measures the intended construct, while reliability guarantees the consistency of measurement results. Instruments that do not meet these criteria can lead to data bias, unreliable conclusions, and inappropriate interventions. Therefore, systematic development instruments, involving experts, and considering local contexts are important factors in improving research quality. This study emphasizes the importance of validity and reliability in measurement to support decision making based on accurate data in the field of guidance and counseling.